Adoptive transfer of cross-protection among alphaviruses in mice requires allogeneic stimulation. - Peck, R (1979)
Cell-mediated (T-effector cell) immunity is proposed as playing the major role in cross-protection between Sindbis and Semliki Forest viruses, which are alphaviruses that do not elicit cross-neutralizing antibodies. In adoptive transfer experiments, T-cells from spleens of Sindbis virus-immunized mice were found to confer specific cross-protection to Semliki Forest virus upon recipient mice. This cross-protection was observed in the outbred ICR strain of mice and when transfers were made between several combinations of inbred and hybrid strains. Cross-protection was substantially reduced if syngeneic rather than allogeneic cell transfers of one spleen equivalent per mouse were made. The results suggest that allogeneic stimulation (mixed lymphocyte reaction in vivo) is necessary to increase the number of effector cells (donor) in the recipient. This was supported by the observation that blastogenic stimulation of donor cells in vitro by concanavalin A induces cross-protection in syngeneic animals. Conversion of recipient cells to specific effector cells also appears to play a role in protecting mice against Semliki Forest virus. This was concluded from the experiments described above, a time course study, and the results of experiments that involved serial passages of transferred cells across histocompatibility barriers. Thus, we propose that both donor and recipient cells are active in protecting recipient mice against challenge with Semliki Forest virus after adoptive transfer.